Amber Alert Effectiveness Reexamined - Griffin, Timothy (Criminal justice policy review, 2022)
Prior research based on limited datasets has suggested AMBER Alerts do little to prevent harm to child abduction victims. However, to investigate the possibility of recent improvements in AMBER Alert performance, the authors examine a sample of 472 AMBER Alerts issued over a 3-year period from 2012 to 2015, using available media accounts to code for relevant case information. The findings are consistent with prior research questioning AMBER Alert effectiveness: The crucial variable predicting Alert outcomes is abductor relationship to the victim, not AMBER Alert “performance.” Furthermore, cases involving “successful” AMBER Alerts are comparable on measurable factors to AMBER Alert cases where the child was recovered safely but the Alert played no role, suggesting both categories of cases involved little real risk. Implications for interpreting the viability of the AMBER Alert concept, public discourse regarding its contribution to child safety, and larger implications for crime control policy are discussed.